Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1976
DOI: 10.4039/ent108601-6
|View full text |Cite
|
Sign up to set email alerts
|

PARASITISM OF THE TARNISHED PLANT BUG, LYGUS LINEOLARIS (HEMIPTERA: MIRIDAE), BY PERISTENUS PALLIPES AND P. PSEUDOPALLIPES (HYMENOPTERA: BRACONIDAE)

Abstract: Can. En?. 108: 601-608 (1976) Life cycles of Perisrenus pallipes (Curtis) and P . pseudopallipes (Loan), parasitoids of the tarnished plant bug, Lygus lineolaris (P. de B . ) , were investigated in an alfalfa field and in uncut weeds in the Ste. Anne de Bellevue area. In 1972, P . pallipes adults emerged in mid-May and P . pseudopallipes adults emerged in late July. The incidence of parasitism in nymphal and adult stages of the tarnished plant bug, L. lineolaris, was measured. The population of the tarnished p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
(8 reference statements)
1
6
0
Order By: Relevance
“…Loan (1965) described the biology of this species under P. pallipes associated with Lygus lineolaris. Lim et al (1976) and our data confirm Loan's biological observations.…”
Section: Peristenus Mellipes (Cresson)supporting
confidence: 92%
See 1 more Smart Citation
“…Loan (1965) described the biology of this species under P. pallipes associated with Lygus lineolaris. Lim et al (1976) and our data confirm Loan's biological observations.…”
Section: Peristenus Mellipes (Cresson)supporting
confidence: 92%
“…cause significant economic damage to stems, leaves, fruits and seeds of a wide variety of crops in North America. Intensive research in Canada and the United States on Lygus bug endoparasitoids showed that euphorine braconid wasps play a role in their control (Ashfaq et al 2004;Braun et al 2001;Broadbent et al1999;Carigan et al 1995;Day 1996Day , 1999Day et al 1990Day et al , 1992Day et al , 1996Day et al , 1998Day et al , 1999Day et al , 2000Day et al , 2003Haye et al 2005Haye et al , 2006Lachance et al 2001;Lim et al 1976;Loan 1965Loan , 1970Loan , 1974aLoan , 1980Loan et al 1976Loan et al , 1987Picket et al 1998Picket et al , 2000Picket et al , 2001Picket et al , 2002Picket et al , 2003Picket et al , 2005Tillmon et al 2000). The endoparasitoids belong to species of Leiophron and Peristenus.…”
Section: Introductionmentioning
confidence: 99%
“…Lygus lineolaris Palisot de Beauvois (Hemiptera: Miridae) is parasitised by four native parasitoids (Hymenoptera: Braconidae) in eastern Canada (Loan 1970;Lim and Stewart 1976;Broadbent, Goulet, Whistlecraft, Lachance, and Mason 1999; Biocontrol Science and Technology, Vol. 18, No.…”
Section: Introductionmentioning
confidence: 99%
“…6, 2008, 583Á590 Sears, Goulet and Mason 2006). Two species, P. mellipes Cresson and P. pseudopallipes Loan, are univoltine and attack Lygus nymphs in the spring and summer, respectively (Lim and Stewart 1976;Goulet and Mason 2006). These species are North American members of the Peristenus pallipes complex, a complex of difficult to distinguish species of Holarctic distribution and are members of the Peristenus mellipies subgroup described in the taxonomic revisions of Goulet and Mason (2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation